Improving Writing Skills By Using PLEASE Strategy of Seventh Grade Students at MTs Nurul Falah Air Mesu Pangkalanbaru - Basri, Samsul (STUDIA: JURNAL HASIL PENELITIAN MAHASISWA, 2016)
The main purposes of this thesis were to know the implementation of PLEASE strategy in improving writing skills and to know whether any significant difference or not in improving writing skills of the students who were taught by using PLEASE strategy. In this thesis the researcher used quantitative approach with quasi-experimental design. The population of the study was all of the seventh grade students of MTs Nurul Falah Air Mesu Pangkalanbaru that consist of 129 students, while the samples of the research were 61 students. The result of the test was analyzed by using statistical analysis of Paired sample t-test and Independent sample t-test. The researcher used Coefficient Correlation and Cronbach Alpha to know the validity and reliability of the test. The result of the observation and documentation were analyzed by using taxonomy analysis and report form. Based on the results of analysis, there were two research findings. First, the students who were taught by using PLEASE strategy (experimental group) had higher score in post-test than the students who were taught by using conventional method (control group). In this case the null hypothesis (Ho) was rejected and the research hypothesis (Ha) was accepted, since t-obtained was 26.097 higher than of the critical value of t-table 2.045 (at the significant level 0.005 in two tailed testing degree freedom 29). While the p-output value was 0.000 lower than 0.005. Seconds the researcher found that most of the students who were taught by using PLEASE strategy had significant improvement in writing skill of descriptive text. Therefore, the PLEASE strategy was one factor in developing students‟ writing skills such as; content, organization, structure, and mechanics. Furthermore, the PLEASE strategy was a way to improve the students‟ writing skill.